Vibrio tapetis, the Causative Agent of Brown Ring Disease, Forms Biofilms with Spherical Components - Rodrigues, Sophie; Paillard, Christine; Le Pennec, Gaël; Dufour, Alain; Bazire, Alexis (Frontiers in Microbiology, 2015)
Vibrio tapetis is a marine bacterium causing Brown Ring Disease (BRD) in the Manila clam Ruditapes philippinarum. V. tapetis biofilm formation remains unexplored although it might be linked to pathogenicity. Our objectives were to characterize the in vitro biofilm formation of V. tapetis and evaluate the effects of culture conditions. Biofilm structure and its matrix composition were examined by confocal laser scanning microscopy and scanning electron microscopy. V. tapetis was able to form biofilms on a glass substratum within 24 h. Polysaccharides and eDNA of the biofilm matrixes were differently distributed depending on the V. tapetis strains. Spherical components of about 1-2 µm diameter were found at the biofilm surface. They contain DNA, proteins, and seemed to be physically linked to bacteria and of cellular nature. Transmission electron microscopy showed that the spherical components seemed to lack a central nucleoid and were devoid of internal compartment. Temperatures > 21°C inhibit BRD whereas low salinity (2%) favor it, none of the both conditions altered V. tapetis ability to form biofilms in vitro. We suggested therefore that biofilm could play a role more in the persistence of the pathogen in clam than in BRD symptoms.